The Routledge handbook of comparative economic systems - Dallago, Bruno, 1950-; Casagrande, Sara (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The Routledge Handbook of Comparative Economic Systems examines the institutional bases of economies, and the different ways in which economic activity can function, be organized and governed. It examines the complexity of this academic and research field, assessing the place of comparative economic studies within economics, paying due attention to future perspectives, and presenting critically important questions, analytical methods and relative approaches. This complements the recent revival of the systemic view of economic governance, which was accelerated by the 2020 pandemic and likely even more the renewed East-West clash epitomized by the Russian invasion of Ukraine and the West's reaction to it. The handbook is divided into five parts. Each part deals with an issue of relevance for the discipline. The first and second parts look at the subject, content and approach of the discipline and its comparative method. The third part looks at the idiosyncratic nature of different economic systems and their constituent elements. The fourth part considers the outcomes that different economic systems generate and how these outcomes change following the evolution and transformation of economic systems. The last part takes stock and looks ahead at the challenges, from a theoretical and applied perspective, and the exogenous and endogenous factors promoting the advancement of the discipline, including the interaction between and competition among varied approaches and opposing paradigms. The handbook brings together leading international contributors to reflect on the relevant debates and case or country studies, provide a balanced overview of the results achieved and current knowledge, as well as evolving issues and new fields of research. The book provides researchers, students and analysts with a complete, critical and forward-looking presentation and analysis of the content, development, challenges and perspectives of comparative economic studies"--
Keywords: Comparative economics; Economics; BUSINESS & ECONOMICS / International / Economics; BUSINESS & ECONOMICS / Economics / Comparative; BUSINESS & ECONOMICS / Economic History